1994
DOI: 10.2190/t0ly-w07y-vvx0-nmap
|View full text |Cite
|
Sign up to set email alerts
|

Death Concern and Attitudes toward the Elderly in Nursing Home Personnel as a Function of Training

Abstract: The present project investigated the relationship between death fear, attitudes toward the elderly, and personal anxiety toward one's own aging in a group of nursing home employees. Contrary to predictions, nursing professionals (i.e., Registered Nurses, Licensed Practical Nurses) did not have higher levels of death concern when compared to Nursing Assistants; in fact, Nursing Assistants had higher levels of death concerns on four components of death fear (fear of the dead, fear of the unknown, fear of conscio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Research in younger populations has suggested a positive association between personal death anxiety and prejudiced attitudes toward older adults, as well as specific fears of one's own aging (DaPaola et al, 1992;DePaola, Neimeyer, & Ross, 1994). Because vulnerable groups sometimes internalize the negative attitudes held about them, we were interested in whether there was evidence of negative attitudes to older adults within this very population and, if so, how this might be related to personal death attitudes.…”
Section: Limitations Of Previous Researchmentioning
confidence: 92%
“…Research in younger populations has suggested a positive association between personal death anxiety and prejudiced attitudes toward older adults, as well as specific fears of one's own aging (DaPaola et al, 1992;DePaola, Neimeyer, & Ross, 1994). Because vulnerable groups sometimes internalize the negative attitudes held about them, we were interested in whether there was evidence of negative attitudes to older adults within this very population and, if so, how this might be related to personal death attitudes.…”
Section: Limitations Of Previous Researchmentioning
confidence: 92%
“…A growing body of literature indicates that such professionals with lower death anxiety may provide higher quality care (DePaola, Neimeyer, & Ross, 1994;Vickio & Cavenaugh, 1985). The topic of death anxiety has become a high priority issue for the education of health professionals (DowneWamboldt & Tamlyn, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The survey-type studies either measured bereavement or grief in relation to a resident in a nursing home (Lesher and Bergey 1988;Pruchno et al 1995) or measured the effect of having a family member in a nursing home on the bereavement experience (Herth 1990;Moss et al 1993;Rudd, Viney, and Preston 1999;Carr et al 2001). Hanson, Danis, and Garrett (1997), Murphy, Hanrahan, and Luchins (1997), and Tolle et al (2000) analyzed the quality of bereavement services in nursing homes, whereas Robbins et al (1992), DePaola, Neimeyer, and Ross (1994), Sumaya-Smith (1995), andLopez McCurdy (1999) measured the effect of working in a nursing home on staff. Findings suggest that losses are hidden in relation to method, but in relation to the review of quantitative research, there was less diversity, a bias toward death, acknowledgement of complexity, a need to focus on wider perspectives, and an apparent focus on emotional response.…”
Section: Findings From Survey Type Researchmentioning
confidence: 99%